Hipolito Unanue - Graña, Francisco (1955)
The largest among the eminent men who filled the stage of the intellectual life of Peru, in that legendary time when the domination of the colony succumbed to the irrepressible independence movement, was undoubtedly Hipólito Unanue, illustrious male, that dazzles us to contemplate his extraordinary and universal personality, and admire your ascendrado love of country, to which he offered up all the fruits of his wisdom, the whole thrust of his optimism and his faith and all the majestic grandeur of his soul.